2009
DOI: 10.1038/npp.2009.23
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Correlates of Brain-derived Neurotrophic Factor Val66Met Polymorphism and Morphometric Abnormalities in Bipolar Disorder

Abstract: The brain-derived neurotrophic factor (BDNF) Val66Met polymorphism has been proposed as a possible candidate for involvement in the pathophysiology of bipolar disorder (BD). To determine whether an association exists between the BDNF Val66Met genotype and morphometric abnormalities of the brain regions involved in memory and learning in BD and healthy subjects. Forty-two BD patients and 42 healthy subjects were studied. Interactions between BDNF Val66Met genotype and diagnosis in gray (GM) volumes were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 86 publications
8
76
1
2
Order By: Relevance
“…The smaller hippocampal volumes in the Val66Met BDNF polymorphism detected in this meta-analysis have been also found in some (Pezawas et al 2004;Matsuo et al 2009;Schofield et al 2009), but not other (Ho et al 2006;Nemoto et al 2006;Joffe et al 2009;Montag et al 2009) studies using voxel-based morphometry. Converging lines of evidence from basic science as well as clinical studies further corroborate the effects of Val66Met BDNF polymorphism on hippocampal volumes.…”
Section: Discussionsupporting
confidence: 70%
“…The smaller hippocampal volumes in the Val66Met BDNF polymorphism detected in this meta-analysis have been also found in some (Pezawas et al 2004;Matsuo et al 2009;Schofield et al 2009), but not other (Ho et al 2006;Nemoto et al 2006;Joffe et al 2009;Montag et al 2009) studies using voxel-based morphometry. Converging lines of evidence from basic science as well as clinical studies further corroborate the effects of Val66Met BDNF polymorphism on hippocampal volumes.…”
Section: Discussionsupporting
confidence: 70%
“…However, the influence of BDNF on brain structure and function was also observed in different cortical regions (Pezewas et al 2004, Matsuo et al 2009, Yang et al 2012). In our study we concentrated on the relation between BDNF polymorphisms and haplotypes with neuropsychological measures engaging predominantly prefrontal cortex, an area associated with higher cognitive functions, such as working memory, executive attention, planning, set-shifting (Bath and Lee 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some research found BDNF genetic effect on cognition to be gender-specific (Matsuo et al 2009, Raz et al 2009, van Wingen et al 2010, Laing et al 2012). In our study the relation between BDNF polymorphisms and TMT_A performance was not modified by gender.…”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor (BDNF) belongs to the neurotrophin superfamily (Matsuo et al, 2009), promotes neuronal survival, and regulates the proliferation and differentiation of nerve cells in the peripheral and central nervous systems (Hartmann et al, 2001). BDNF serves an important role during brain development and in synaptic plasticity (Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%